Load Balancing Technique in Body Area Network by Utilization of Smart Node - Singh, Jatinder; Saini, Navjeet; Kaur, Sandeep (International Journal of Computer Sciences and Engineering, 2019)
There are many techniques used to enhance the network life time each depends upon the number of nodes deployed, a parent node, path followed, energy of the nodes and the forward nodes. The selection of forward node is based on cost equation, the total load to this node is maximum and there is a chance of path loss because the distance between the nodes is in feet which may cause data loss. In this paper we proposed model having a forwarder node, which selection is based on cost function and two fixed data transfer nodes. The purpose is to implement the concept of multilevel, multi-hop and a smart node which divides the load and helps to smooth transfer of data with high stability. The major benefit of this new designed methodology is to increase the network life time by enhancing the throughput, by minimizing the path loss or data loss and maximum packet delivering to the sink.